Optimalisasi Pelayanan Publik dan Pemberantasan Korupsi Melalui Peningkatan Penerapan Sistem PTSP - Destamara, Aster Sharon (Proceedings Series on Social Sciences & Humanities, 2024)
Public services from the government such as PTSP (Pelayanan Terpadu Satu Pintu) are expected to run effectively and be one way to improve the institution's good image for the community. The establishment of the PTSP institution, the regions can process service permits and non-licensing. This form of simplification is in the form of shorter procedures for applying for permits and more administration-based retribution rationalization. But on the other hand, the practice of corruption is very vulnerable to occur in the field of service licensing, due to the intensity of face-to-face meetings between business actors and government officials. In this case, state administrative law plays an important role as a deterrent and supervisor of state administration institutions from corrupt practices. The purpose of this study is to analyze the effectiveness of PTSP implementation as well as Corruption prevention efforts are viewed from the perspective of State Administrative Law The research method used is a normative legal methodology taken from various literature sources.